PENGEMBANGAN MEDIA KOMIK MATEMATIKA BERBASIS BUDAYA (KOMATISA) SEBAGAI PENGUATAN DIMENSI BERNALAR KRITIS SISWA KELAS IV - Amalia, Putri Kharisma; Ermawati, Diana; Masfuah, Siti (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2024)
This research is motivated by the lack of innovative learning media at SD 2 Gamong which results in the lack of critical reasoning abilities of class IV students, so research is needed that can strengthen students' critical reasoning abilities through innovative learning media. This research aims to measure the validity and effectiveness of culture-based mathematics comic media in strengthening the Pancasila Student Profile, the dimensions of students' critical reasoning. This research uses the Research and development (R&D) research model according to Borg and Gall which has been adapted by Sugiyono. The subjects of this research were 17 grade IV students at SD 2 Gamong. Data collection techniques in this research are questionnaires and tests. Data analysis in this research is product validation, normality test and T-test. The product validation results show that the material expert validator results are 92.65% and the media expert validator results are 98.5% in the very feasible category. The product effectiveness results show a normal data distribution with a sig value > 0.05, a T-test result of 0.000 is obtained which shows there is a significant difference. This shows that the development of culture-based mathematical comic media is very feasible and effective for use in learning.